Market ranking and network structure: pathway to dominance. Issue 1 (15th June 2021) - Sarabi, Yasaman; Smith, Matthew; McGregor, Heather; Christopoulos, Dimitris
Abstract : Purpose: The relationship between interlocking directorates and firm performance has been increasingly debated, with a focus on whether firm's centrality in interlock networks is associated with performance. The purpose of this study is to examine not only how a firm's position in this network is associated with performance but also how the performance of network partners can impact a firm's performance. This study examines how firms effectively utilise the interlock network to achieve the goal of higher market capitalisation – termed market capitalisation rank (MCR). Design/methodology/approach: The premise of the study is the UK FTSE 350 firms from 2014 to 2018. The paper makes use of a temporal network autocorrelation model to examine how firm characteristics, the structural position in the interlock network and the performance of network partners affect MCR over time. Findings: The analysis indicates that firms with ties (via the interlock network) to firms with high market capitalisation are more likely to enhance their own MCR, highlighting network partners have the opportunity to play a critical role in a firm's dominance strategy to optimise firm value. Originality/value: The value of this research is that it does not only look at the impact of a firm's position in the network on performance, but the impact of the performance of network partners on a firm's market performance as well.